Limit, difference and relation as constitutive principles of transcendental discourse: deconstructive context - Ilyina, Anna (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2017)
At the heart of this study is an analysis of the concepts of limit, difference and relation in the context of their significance and function in transcendental discourse problem. At the same time as a conceptual core of “rigoristic” transcendentalism along with Kant’s philosophy author also considers Husserl’s phenomenology and Derrida’s deconstruction. In the course of analysis author reveals to what extend and in what aspects the concepts of limit, difference and relation as fundamental principles of transcendental thinking determine a transcendental paradigm in its essential features. The article deals with diverse embodiment modes of these concepts within both the framework of transcendental paradigm as a whole and the particular versions of transcendentalism. Regarding the limit, such semantic kinds of this concept in transcendental discourse as restriction, distinction, impossible passage are fixed. As for categories of relation and difference the author proposes to consider them as mutually complementary principles. It is argued, that on the grounds of dominant position of such the principles a transcendental thinking can oppose itself to substantialist paradigm, which reduce the relation to Thing and the Other to One (identical, indivisible, single). The article shows how in virtue of synthesis of ideas of unreduced difference and (im)possible passage the Derridean concept of quasi-transcendental is constituted, revealing Derrida’s critical succession with respect to transcendental legacy.